Physical Activity, Immune System, and the Microbiome in Cardiovascular Disease - Fernandez, Dawn M.; Clemente, Jose C.; Giannarelli, Chiara (Frontiers in Physiology, 2018)
Cardiovascular health is a primary research focus, as it is a leading contributor to mortality and morbidity worldwide, and is prohibitively costly for healthcare. Atherosclerosis, the main driver of cardiovascular disease, is now recognized as an inflammatory disorder. Physical activity may have a more important role in cardiovascular health than previously expected. This review overviews the contribution of physical activity to cardiovascular health, the inflammatory role of atherosclerosis, and the emerging evidence of the microbiome as a regulator of inflammation.